Teologi Pembebasan Menurut Asghar Ali Engineer - Syamsuddin, M. Mukhtasar (Jurnal Filsafat "WISDOM", 2000)
This research is intended a.tt an attempt to disclose the meaning of theology of liberation and its relevance in the context of plurality of' religions in Asia. The meaning and the relevance will be analyzed according to the notion ofAsghar Ali Engineer, a Muslim theolog borned in India who has vigorous mind and revolutionary attitude in working. This research used in the effort to actualize the theological transformative-revolutionary meanings, especially for Islamic theology to face the problematic of contemporary human lifeThe thought concept ofAsghar Ali in the context ofthe plurality ofreligion.s inAsia, in this research is analyzed by philosophy ofreligion approach. The following methods are applied in this research, that· are; historical continuity, analysis and synthesis, interpretation, and description.The results ofthi.tt research show that the fundamental problems ofthe Asghar Ali's theology of liberation in the context oj' the plurality of religions as its background, relate to the attempt to formulate thereltgionmeantng (essence) in the human life. The problems maintain all of the ·theological, human, and justice dimensions. The thought of Asghar Ali about theology of liberation is constructed in  the frame ofreligion (Islam) values that are centralized on the tauhid· concept by its moral vision. The thought is intended to realize a universal brotherhood,equality,  and social justice. Interreligious dialogue and theactiono! the religions in Asia, therefore implemented through the basical paradigm in the frame ofthat value and mottol vision.